2018
DOI: 10.1094/pdis-03-18-0466-re
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pre- and Postanthesis Applications of Demethylation Inhibitor Fungicides on Fusarium Head Blight and Deoxynivalenol in Spring and Winter Wheat

Abstract: Anthesis is generally recommended as the optimum growth stage for applying a foliar fungicide to manage Fusarium head blight (FHB) and the Fusarium-associated toxin deoxynivalenol (DON) in wheat. However, because it is not always possible to treat fields at anthesis, studies were conducted to evaluate pre- and postanthesis treatment options for managing FHB and DON in spring and winter wheat. Network meta-analytical models were fitted to data from 19 years of fungicide trials, and log response ratio ([Formula:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Several tillers on a wheat plant can develop fertile spikes and shed pollen across a range of days as all of these tillers are not at the same development stage during heading and anthesis (Kiesselbach and Sprague, 1926;Noversoke, 2014;Tilley et al, 2019). More uniform spike development could lead to more uniform anthesis and better fungicide efficacy, as current fungicides (prothioconazole + tebuconazole and metconaxole) have been shown to reduce FHB incidence by only approximately 50% compared to a non-treated control (Paul et al, 2018). Phosphorus can be applied in a variety of placements in the soil during fall application; however in-furrow application at planting has been shown to result in greater grain yield compared to broadcast application (Peterson et al, 1981;Fiedler et al, 1989;Grant et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Several tillers on a wheat plant can develop fertile spikes and shed pollen across a range of days as all of these tillers are not at the same development stage during heading and anthesis (Kiesselbach and Sprague, 1926;Noversoke, 2014;Tilley et al, 2019). More uniform spike development could lead to more uniform anthesis and better fungicide efficacy, as current fungicides (prothioconazole + tebuconazole and metconaxole) have been shown to reduce FHB incidence by only approximately 50% compared to a non-treated control (Paul et al, 2018). Phosphorus can be applied in a variety of placements in the soil during fall application; however in-furrow application at planting has been shown to result in greater grain yield compared to broadcast application (Peterson et al, 1981;Fiedler et al, 1989;Grant et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…One of the more significant findings was that summaries over windows which crossed anthesis were better input predictors than summaries that were restricted to either side of anthesis; our earlier modelling efforts generally focused on pre-anthesis weather with the objective of providing FHB predictions before anthesis so that fungicides could be applied [27]. However, post-anthesis fungicide applications against FHB may also be effective [31]. Functional modelling, as we have shown, can be useful in the process of developing simple (lr) models that are at least as good as existing models, that make use of novel predictors, and which add to the pool of existing models to choose from.…”
Section: Discussionmentioning
confidence: 99%
“…Reports indicated that efficient fungicide spraying significantly reduces FHB intensity and DON levels and increased both yield and thousand kernel weight, when compared to untreated controls (Nicholson et al,199). As shown, DON contamination in grains is directly related to FHB intensity (Blandino et al, 2006;Haidukowsky et al, 2005;Paul et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Quantitative damages caused by FHB, after no-till has been widely used by growers can be as high as 39.8% (Casa et al, 2004(Casa et al, , 2011. In addition to the quantitative damage, the qualitative due to the grains contamination by mycotoxins is equally important (Paul et al, 2007(Paul et al, , 2018. There are reports showing that the reduction of mycotoxin content related to FHB chemical control, i.e., as control increases deoxynivalenol (DON) contamination decreases (Haidukowsky et al, 2016).…”
Section: Introductionmentioning
confidence: 99%